Im Gold- und Silberland - Twain, Mark, 1835-1910; Richter, Albert B., 1845-1898 (Salt Lake City, UT : Project Gutenberg, 2021)
"Im Gold- und Silberland" by Mark Twain is a humorous narrative written in the early 20th century. The book recounts the adventures and misadventures of a character navigating the burgeoning mining town of Carson City, Nevada, during the gold and silver rush era. It combines vivid depictions of the frontier life with Twain's characteristic wit and social commentary, providing a microscopic view of the human condition amid the chaos of a new American frontier. The opening of the text introduces us to the difficult yet colorful life in Carson City as the narrator and his companion arrive in a makeshift mining town. Here, they encounter eccentric local characters and experience the dramatic dust storms called "Washoe Zephyrs" that characterize the region. The narrator reflects on various humorous situations, like witnessing a confrontation involving gunplay and being introduced to the chaotic lifestyle of the miners and townsfolk. The narrative sets the tone for a quirky adventure filled with satire, ultimately showcasing the absurdities of human behavior in the pursuit of wealth in the wild and untamed landscape of 19th-century America. (This is an automatically generated summary.)
Translations from: Roughing It.
Release date is 2021-04-16
The Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: West (U.S.) -- Description and travel; Twain, Mark, 1835-1910 -- Travel -- West (U.S.); Authors, American -- Homes and haunts -- West (U.S.); West (U.S.) -- Intellectual life -- 19th century